2021
DOI: 10.3390/healthcare9091199
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Primary and Middle School Teachers’ Problematic Internet Use and Fear of COVID-19 on Psychological Need Thwarting of Online Teaching and Psychological Distress

Abstract: Problematic Internet use (PIU) is a risk factor for psychological distress during COVID-19, as teachers are a psychologically vulnerable population. We explored the role of PIU in terms of primary and middle school teachers’ fear of COVID-19 and psychological need thwarting (PNT) of online teaching. We empirically evaluated the relationships among these research variables in explaining teachers’ psychological distress during COVID-19. Online survey data were collected from 9,030 teachers. A high proportion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
58
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(64 citation statements)
references
References 78 publications
(185 reference statements)
6
58
0
Order By: Relevance
“…Correlations between cyberchondria and Internet addiction were consistent with previous studies 1–3,10,12,16,17,42 . A prolonged Internet search for health‐related information disrupts other Internet searches and other daily activities; 39 thus, cyberchondria may lead to Internet addiction 22 . Originating from fear and anxiety related to COVID‐19, current students may keep surfing the Internet for COVID‐19 health‐related information, 39 resulting in Internet addiction.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Correlations between cyberchondria and Internet addiction were consistent with previous studies 1–3,10,12,16,17,42 . A prolonged Internet search for health‐related information disrupts other Internet searches and other daily activities; 39 thus, cyberchondria may lead to Internet addiction 22 . Originating from fear and anxiety related to COVID‐19, current students may keep surfing the Internet for COVID‐19 health‐related information, 39 resulting in Internet addiction.…”
Section: Discussionsupporting
confidence: 85%
“…[1][2][3]10,12,16,17,42 A prolonged Internet search for health-related information disrupts other Internet searches and other daily activities; 39 thus, cyberchondria may lead to Internet addiction. 22 Originating from fear and anxiety related to COVID-19, current students may keep surfing the Internet for COVID-19 healthrelated information, 39 resulting in Internet addiction. A repetitive Internet search for health-related information such that related to COVID-19 is a feature of cyberchondria.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have examined the psychological distress (especially in anxiety and depression) during the COVID-19 pandemic (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). Specifically, Ahorsu et al (18) and Pramukti et al (26) found that university students have issues of anxiety and suicidal ideation during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%